2006
DOI: 10.1017/s0022112006000711
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulations of bifurcations in an air-filled rotating baroclinic annulus

Abstract: Three-dimensional Direct Numerical Simulation (DNS) on the nonlinear dynamics and a route to chaos in a rotating fluid subjected to lateral heating is presented here and discussed in the context of laboratory experiments in the baroclinic annulus. Following two previous preliminary studies by Randriamampianina (2002, 2003), the fluid used is air rather than a liquid as used in all other previous work. This study investigated a bifurcation sequence from the axisymmetric flow to a number of complex flows.The tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
3
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 51 publications
(127 reference statements)
6
44
3
4
Order By: Relevance
“…As such, the figure is a bifurcation diagram representing the sequence of three basic solutions, the axisymmetric solution on the x-axis and the m = 2 and m = 3 solutions pro- jected onto the same plane. The instability of the axisymmetric solution and the m = 2 solution branch are reproduced from the earlier study in Randriamampianina et al (2006). The present study focusses on evolution of the m = 3 solution branch when increasing progressively the rotation rate up to T a = 5.…”
Section: The Numerical Modelsupporting
confidence: 60%
“…As such, the figure is a bifurcation diagram representing the sequence of three basic solutions, the axisymmetric solution on the x-axis and the m = 2 and m = 3 solutions pro- jected onto the same plane. The instability of the axisymmetric solution and the m = 2 solution branch are reproduced from the earlier study in Randriamampianina et al (2006). The present study focusses on evolution of the m = 3 solution branch when increasing progressively the rotation rate up to T a = 5.…”
Section: The Numerical Modelsupporting
confidence: 60%
“…The radial, azimuthal and vertical (or axial) coordinates are denoted r, ϕ and z, respectively, with unit vectors e r , e ϕ and e z . This model is essentially the same as those used in many previous numerical studies, including, for example, [23,2,24,17,12]. With air as the working fluid, it is expected that the Boussinesq approximation will lead to quantitatively accurate results for ∆T < 50 [12], while above this, the results may only be qualitatively accurate.…”
Section: Model Equationsmentioning
confidence: 99%
“…Although many of the features of the flow transitions are similar to those observed at other Prandtl numbers, it was found that the Prandtl number played an important role in some transitions. In particular, hysteresis is observed along the transition from axisymmetric to steady waves [12], and the onset of amplitude vacillation is found to occur as rotation rate is increased. The experiment also showed the existence of weak (low-amplitude) steady waves over large areas of parameter space.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations